2008
DOI: 10.1002/da.20373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of posttraumatic stress disorder among Kuwaiti military men according to level of involvement in the first Gulf War

Abstract: First, to compare the prevalence and intensity of posttraumatic stress disorder (PTSD) among Kuwaiti military men, divided into four groups (50 subjects each) according to degree of exposure to war trauma: (1) the retired (retired before the invasion); (2) an active-in-the-army group (AIA) (involved in duties at the rear only); (3) an in-battle (IB) group (involved in combat); and (4) prisoners of war (POWs-captured during combat). Second, to compare the severity of impact of event, comorbid depression, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Findings from cross-sectional studies appear to be consistent in that there is a small to medium negative relationship between self-esteem and posttraumatic stress symptoms (e.g., Al-Turkait & Ohaeri, 2008; Li et al, 2009), indicating that subjects with higher self-esteem experience traumatic stress to a lesser extent. In addition, several studies have reported significant negative associations between self-esteem and childhood adversities (e.g., Stein et al, 2002; Vigil et al, 2010), with the highest negative association found between childhood emotional abuse/emotional neglect and self-esteem (Finzi-Dottan & Karu, 2006; Kuo et al, 2011).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Findings from cross-sectional studies appear to be consistent in that there is a small to medium negative relationship between self-esteem and posttraumatic stress symptoms (e.g., Al-Turkait & Ohaeri, 2008; Li et al, 2009), indicating that subjects with higher self-esteem experience traumatic stress to a lesser extent. In addition, several studies have reported significant negative associations between self-esteem and childhood adversities (e.g., Stein et al, 2002; Vigil et al, 2010), with the highest negative association found between childhood emotional abuse/emotional neglect and self-esteem (Finzi-Dottan & Karu, 2006; Kuo et al, 2011).…”
Section: Resultsmentioning
confidence: 82%
“…The cross-sectional findings regarding locus of control are inconsistent. The vast majority of the studies that we reviewed report a small to medium positive relationship between an external locus of control and traumatic stress (Al-Turkait & Ohaeri, 2008; Kuterovac-Jagodic, 2003; Maercker & Herrle, 2003; Mellon et al, 2009; Weiss et al, 1995). That is, individuals who do not feel in control over the events in their lives tend to be affected by posttraumatic symptoms to a greater degree.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the psychological outcomes of war, conducted in various settings and cultures, have mainly focused on adverse effects, the most common of which is PTSD (e.g., Al-Turkait and Ohaeri 2008;Dyregrov et al 2002;Galea et al 2003;Thabet and Vostanis 2000;Yaswi and Haque 2008). A similar tendency can be found in studies conducted in Israel (e.g., Palmieri et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Second, it has been shown to have cross-cultural equivalence between Western European and Arabic populations [53]. Third, the HSCL-25 has been used in Kuwait in general population and clinical settings [57,58], and an Arabic translation already exists. Finally, there are no reports on the factor structure of the HSCL-25 [59].…”
Section: Introductionmentioning
confidence: 99%